2015
DOI: 10.1002/nau.22800
|View full text |Cite
|
Sign up to set email alerts
|

Electronic bladder diaries of differing duration versus a paper diary for data collection in overactive bladder

Abstract: For future OAB trials, 7-day or continuous electronic diaries may improve accuracy and reliability of micturition and incontinence frequency data compared with shorter collection periods and paper diaries. Neurourol. Urodynam. 35:743-749, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Therefore, it may be of interest to see if the clinical benefit and HRQOL improvements seen in this study are reflected in real‐life clinical practice. A further consideration is that our study used 7‐day electronic diaries, which had previously been reported as having a higher reliability and accuracy for measuring micturition and incontinence in OAB patients compared with traditional 3‐day paper diaries . However, previous combination studies, including BESIDE and SYMPHONY, used 3‐day electronic diaries; therefore differences in the use of patient diaries may partially have contributed to differences in the efficacy outcomes between the studies …”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it may be of interest to see if the clinical benefit and HRQOL improvements seen in this study are reflected in real‐life clinical practice. A further consideration is that our study used 7‐day electronic diaries, which had previously been reported as having a higher reliability and accuracy for measuring micturition and incontinence in OAB patients compared with traditional 3‐day paper diaries . However, previous combination studies, including BESIDE and SYMPHONY, used 3‐day electronic diaries; therefore differences in the use of patient diaries may partially have contributed to differences in the efficacy outcomes between the studies …”
Section: Discussionmentioning
confidence: 98%
“…More novel approaches may incorporate a patient's “vote” for a program or a setting based on bowel/bladder diaries kept in real time. There are already available smart‐phone applications for patients to track their symptoms which may be utilized in device programming …”
Section: Future Researchmentioning
confidence: 99%
“…There are already available smart-phone applications for patients to track their symptoms which may be utilized in device programming. 170 Economic modeling suggests that SNM becomes costeffective relative to intradetrusor botulinum toxin injections for idiopathic OAB after about 5 years of treatment. 171 At 10 years, models suggest that SNM is also cost-effective relative to oral medical therapy for OAB.…”
Section: Future Researchmentioning
confidence: 99%
“…Traditionally, paper‐based frequency‐volume charts have been used, although compliance with this reporting system having recently been questioned . In comparison, the actual compliance with electronic bladder diaries was 90% to 94% . However, participants were asked to complete their diaries, such as voided volume, as soon as possible after their events.…”
Section: Discussionmentioning
confidence: 99%
“…However, the usefulness of the information obtained from these charts is dependent on the reliability of the recordings and duration of monitoring . Moreover, these charts are time‐consuming to complete, resulting in a low adherence rate of recording . Electronic bladder diaries have been developed to overcome the limitations of paper charts; however, these devices still require data input, including voided volume from the patient .…”
Section: Introductionmentioning
confidence: 99%